ANALYSIS OF CRIMINAL ACTS AGAINST MINORS: A STUDY OF THE CASE OF THE MURDER OF A USTAZAH IN LAKE RANGAS - Adelia Dwi Karsanegara; Achmad Adi Surya G; Rizki Setyobowo Sangalang (RADJA PUBLIKA, 2026)
This study examines juvenile crime through a case study of the murder of a female Islamic teacher in Danau Rangas, Palangka Raya. A qualitative approach was used to examine the factors contributing to the thirteen-year-old perpetrator's behavior, including emotional distress, environmental influences, and poor communication within Islamic boarding schools. The results indicate that feelings of revenge and exposure to digital violence contribute to the child's aggressive behavior. Furthermore, the implementation of Law Number 11 of 2012 concerning the Juvenile Criminal Justice System demonstrates how the principle of restorative justice is implemented through social assistance, cross-agency coordination, and avoidance of detention. This study emphasizes that a legal approach to children needs to be balanced with attention to their psychological and social well-being for the effective development process.